2008
DOI: 10.1152/ajpendo.90704.2008
|View full text |Cite
|
Sign up to set email alerts
|

Bis deficiency results in early lethality with metabolic deterioration and involution of spleen and thymus

Abstract: Bcl-2 interacting cell death suppressor (Bis), also known as Bag3 or CAIR-1, is involved in antistress and antiapoptotic pathways. In addition to Bcl-2, Bis binds to several proteins, suggesting it has diverse functions in normal and pathological conditions. To better define the physiological function of Bis in vivo, we developed bis-deficient mice with a cre-loxP system. Targeted disruption of exon 4 of the bis gene was demonstrated by Southern blotting and PCR, and Western blotting showed that no intact or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 35 publications
3
38
0
Order By: Relevance
“…Experimental mouse model The heterozygous mutant BIS-HT mice were prepared as previously described [24] and maintained on a C57/BL6 background to generate BIS-HT and Bis-wild-type (BIS-WT) littermates. Only male BIS-HT and BIS-WT mice were used for the studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental mouse model The heterozygous mutant BIS-HT mice were prepared as previously described [24] and maintained on a C57/BL6 background to generate BIS-HT and Bis-wild-type (BIS-WT) littermates. Only male BIS-HT and BIS-WT mice were used for the studies.…”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated that the deletion of the Bis gene (also known as Bag3) in mice results in growth retardation and early lethality with serious metabolic deterioration [24,25], suggesting that BIS is critical for postnatal growth and survival. In contrast to Bis-knockout mice, the growth and reproduction of Bis -heterozygote ([Bis +/− ]; BIS-HT) mice appeared to be normal.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Bis has also been implicated in the anti-stress pathway, since it shows a concomitant induction with Hsp70 in cells exposed to stressful stimuli, such as heat shock or exposure to heavy metals [23], and functions as a co-chaperone for the Hsp70 regulating degradation of HSP client proteins [24]. We previously reported that a functional lack of Bis by the cre-loxP mediated targeting of exon4 leads to growth retardation, decreased white blood cell (WBC) levels in the blood and postnatal death before 3 weeks [25]. In the present study, we explored the hematopoietic systems of mutant mice and identified multiple hematological derangements that originate from their defective microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…As itemized in Table 1 and discussed above, various mouse models have revealed important cell and matrix players in the HME, while others have implicated the importance of proper cell cycle (Walkley et al 2005;), transcription (Corradi et al 2003;Purton et al 2006;Kieslinger et al 2010), cell-cell communication (Larsson et al 2008), and survival signals (Youn et al 2008;Kwon et al 2010) in the HME (Table 1). Still, the exact cellular make up and location of the HME is continually under debate, though most agree the cells of the osteoblast and vascular niches are important players in hematopoiesis.…”
Section: Summary and Perspectivesmentioning
confidence: 99%